Comparison of AH26 Physicochemical Properties with Two AH26/Antibiotic Combinations - Razmi, Hasan; Parvizi, Shaghayegh; Khorshidian, Azam (Iranian Endodontic Journal, 2010)
INTRODUCTION: The purpose of this study was to compare the setting time and post-setting solubility, flow, film thickness and dimensional changes of AH26 root canal sealer with AH26-Antibiotic combination. MATERIALS AND METHODS: This study was performed according to British standard BS 6876 (2001) which tests the physicochemical properties of endodontic sealers. Three samples of each of tested materials including AH26 alone, AH26/amoxicillin and AH26/doxycycline were used to test each of the properties. They were prepared according to ISO protocols. RESULTS: The setting time of studied materials was 46 hours for AH26, 29 hours for AH26/amoxicillin, 49 hours for AH26/doxycycline. Flow test results were as follows, for AH 26, 15.6 mm; AH26/amoxicillin, 14.9 mm; AH26/doxycycline, 14.2 mm. Film thickness was 0.024 mm in AH26, 0.0283 mm in AH26/amoxicillin, 0.0276 mm AH26/doxycycline. The solubility of AH26 was 0.0076%, AH26/amoxicillin, 0.0113%, and for AH26/doxycycline, 0.013 %. Dimensional changes following setting was 0.07 mm, 2.6 mm, and 1.1 mm for AH 26, AH26/amoxicillin, and AH26/doxycycline, respectively. CONCLUSION: The physico-mechanical properties of AH26 antibiotic combinations were superior compared with AH26, with the exception of flow. Also, AH26/amoxicillin had a lower setting time than AH26. However, all values were within an acceptable range which conformed to ISO.